درجة تضمُّن قيم المواطنة الرقمية في المناهج الدراسية من وجهة نظر أعضاء هيئة التدريس بكليات تقنية الحاسوب والمعلومات (Albayan Scientific Journal, 2023)
This study aimed to identify the degree of including the values of digital citizenship that in the Scholastic curricula from the point of view of the faculties member's staff in the Faculties of Computer and Information Technology in Libyan higher education institutions. and exploration whether there is a difference in the degree of including the values of digital citizenship that in the Scholastic curricula from the point of view of the faculties member's staff. According some of their demographic and functional variables.   And it results showed that the values of digital citizenship in the Scholastic curricula were including to a moderate degree from the viewpoint of the faculties member's staff, where its total Arithmetic averages reached (2.91). Moreover, the results showed that it is no different in the degree of including the values of digital citizenship which at the Scholastic curricula from the point of view of the faculties member's staff According their demographic and functional variables.   The study recommended that the Scholastic curricula must focus on clarifying the importance of time management style to students when they using digital technology due to avoiding the risks of addiction to it, And. It also recommended that the Scholastic curricula have to expand student's skills in choosing strong passwords for their accounts on different websites.